ANALISIS PENGELOLAAN ADMINISTRASI PENDIDIKAN DI TK ISLAMI TERPADU ADZKIA ISLAMI DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Dinda Oktarini; Aliyah Aliyah; Shera Shera; Vinna Asta Rani; Riza Urzila; Desi Aryani; Dewi Masriah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the management of educational administration at Adzkia Integrated Islamic Kindergarten in improving learning effectiveness. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research informants consisted of the principal and teachers, while supporting data were obtained from various school administrative documents, including organizational structure records, semester programs, Daily Learning Implementation Plans (RPPH), financial reports, and children's developmental report cards. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, while source and method triangulation were applied to ensure data validity. The findings reveal that Adzkia Integrated Islamic Kindergarten has implemented educational administration management systematically, covering curriculum administration, student administration, personnel administration, facilities and infrastructure management, and financial administration. The implementation of the Merdeka Curriculum is supported by comprehensive administrative documents, such as semester programs, daily learning plans, and assessment and reporting systems for children's development. Human resource management is carried out through clear task distribution, teacher training programs, and principal supervision. Financial management, including the utilization of School Operational Assistance (BOS) funds, is conducted transparently and accountably through systematic planning, recording, and reporting processes. Furthermore, a well-functioning organizational structure and regular administrative monitoring contribute to the smooth implementation of educational programs. However, the limited number of educational staff requires teachers to perform multiple administrative responsibilities. Therefore, additional administrative personnel and strengthened human resource capacity are needed to further enhance learning effectiveness and improve the quality of early childhood education services. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengelolaan administrasi pendidikan di TK Islam Terpadu Adzkia dalam meningkatkan efektivitas pembelajaran. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Informan penelitian terdiri atas kepala sekolah dan guru, sedangkan data pendukung diperoleh dari berbagai dokumen administrasi sekolah, seperti struktur organisasi, program semester, RPPH, laporan keuangan, dan rapor perkembangan anak. Analisis data dilakukan melalui tahap reduksi data, penyajian data, dan penarikan kesimpulan dengan menggunakan triangulasi sumber dan metode untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa TK Islam Terpadu Adzkia telah melaksanakan pengelolaan administrasi pendidikan secara sistematis yang meliputi administrasi kurikulum, peserta didik, tenaga pendidik, sarana prasarana, dan keuangan. Implementasi Kurikulum Merdeka didukung oleh dokumen administrasi yang lengkap, seperti program semester, RPPH, serta sistem penilaian dan pelaporan perkembangan anak. Pengelolaan sumber daya manusia dilakukan melalui pembagian tugas yang jelas, pelatihan guru, dan supervisi kepala sekolah. Pengelolaan keuangan, termasuk pemanfaatan Dana BOS, dilaksanakan secara transparan dan akuntabel melalui perencanaan, pencatatan, serta pelaporan yang teratur. Struktur organisasi sekolah yang berjalan baik serta pengendalian administrasi yang dilakukan secara berkala turut mendukung kelancaran pelaksanaan program pendidikan. Meskipun demikian, keterbatasan jumlah tenaga pendidik menyebabkan guru masih merangkap beberapa tugas administrasi. Oleh karena itu, diperlukan penambahan tenaga administrasi serta penguatan kapasitas sumber daya manusia agar efektivitas pembelajaran dan mutu layanan pendidikan anak usia dini dapat terus ditingkatkan secara optimal.